A retrospective comparative analysis of two different techniques of small bowel diversion in Ileal perforation cases: a single centre experience - Suryavanshi, Parijat; rai, Anurag; suryavanshi, Abhishek; singh, Rupali (International Journal of Medical Research and Review, 2016)
Introduction: Ileal perforation is a common surgical emergency especially in Indian sub-continent due to increased incidence of enteric fever and tuberculosis- two most common causes of ileal perforation. Many different techniques had been applied for treatment of perforation like primary closure, exteriorization of perforation site or primary closure with proximal diversion stoma. Many cases are not suitable for primary closure; in such cases ileostomy is done. Ileostomy is associated with significant morbidity which adds to financial burden and decreases quality of life. Tube ileostomy has been explored as an alternative to conventional ileostomy sans its morbidity. Methods: Here we retrospectively analyzed ileal perforation cases treated with either loop ileostomy or tube ileostomy at our centre during last 3 years. Result: A total of 50 ileal perforation cases treated with ileostomy either tube ileostomy ( n = 21) or conventional loop ileostomy (n = 29 ) were included for study and their immediate and late post operative complications were recorded and analysed. Conclusion: We found that tube ileostomy is a safe and effective mode of diversion and is associated with minimal stoma related morbidity like peristomal excoriation, hernia, retraction, prolapse, obstruction etc.